Ellipsometry of Functional Organic Surfaces and Films (Springer Series in Surface Sciences,, 2018)
This new edition provides a state-of-the-art survey of ellipsometric methods used to study organic films and surfaces, from laboratory to synchrotron applications, with a special focus on in-situ use in processing environments and at solid-liquid interfaces. Thanks to the development of functional organic, meta- and hybrid materials for new optical, electronic, sensing and biotechnological devices, the ellipsometric analysis of optical and material properties has made tremendous strides over the past few years. The second edition has been updated to reflect the latest advances in ellipsometric methods. The new content focuses on the study of anisotropic materials, conjugated polymers, polarons, self-assembled monolayers, industrial membranes, adsorption of proteins, enzymes and RGD-peptides, as well as the correlation of ellipsometric spectra to structure and molecular interactions.